Prophylactic Tracheal Stenting for the Palliation of Anaplastic Thyroid Carcinoma. (2nd September 2014) - Mathew, Rajeev; Varadharajan, Kiran; Hay, Ashley; Williamson, Peter A.; Odutoye, Babtunde; Madden, Brendan
Abstract : Objectives: (1) Determine if airway stenting in patients with anaplastic thyroid carcinoma (ATC) is effective in preventing and treating shortness of breath. (2) Analyze whether this procedure affects survival. Methods: Retrospective case note analysis of patients diagnosed with ATC from 2003 to 2013 at a tertiary head and neck unit. Patients diagnosed with ATC were stented with an expandable covered metallic stent, irrespective of airway symptoms, provided they were medically fit and the tumor was >1 cm distal to the vocal cords. Outcome measures were development of dyspnea and survival. Results: Twelve patients were identified. Tracheal stenting was performed successfully in 4 out of 5 patients; the procedure was abandoned in 1 case due to gross airway distortion. Three of the 4 stented patients did not have airway compromise at the time of stenting; of these 3 patients, 1 did not develop airway compromise at all. The other 2 later developed acute dyspnea due to stent migration as a result of tumor in‐growth; these were successfully managed with stent exchange. All nonstented patients died with or from dyspnea. Mean survival postdiagnosis in stented patients was 89 days (n = 4; range, 39‐189 days) and in nonstented patients was 91 days (n = 9; range, 8‐233). Conclusions: Tracheal stenting is safe and effective at treating and preventing distressing airway symptoms in patients with ATC. It does not, however, confer any survival benefit.